Clinical experience in the treatment of spinal cord tumors with cyberknife® fractionated stereotactic radiotherapy (Annals of Medical Research, 2021)
Aim: The aim of the study is to evaluate the efficacy and safety of Cyberknife® fractionated stereotactic radiotherapy (FSRT) in spinal cord tumors. The secondary aim is to present short-term local control of the patients with spinal cord tumors.Materials and Methods: Ten patients with spinal cord tumors who underwent FSRT between January 2010 and May 2014 were retrospectively analyzed. FSRT was administered in a median dose of 20 Gy (range, 16-40 Gy) in a median 5 fractions (range, 4-6 fractions). Radiological / pathological diagnoses of the patients are meningioma (n = 3), schwannoma (n = 1), neurofibroma (n = 1), hemangioblastoma (n = 1), chordoma (n = 1), recurrent medulloblastoma (n = 1), recurrent ependymoma (n = 2). Results: The median age was 57 years (range, 22-84 years). The median tumor volume was 3.3 cm3 (range, 1.8- 74 cm3). Tumor localization was cervical in six cases, lumbar in three cases, and thoracic in one case. The median follow-up time was 13 months (range, 3-48 months). Clinical improvement was observed by FSRT in all patients except the three cases. Tumor control (no progression) was achieved in all cases. Radiologically, 6 patients were stable, 2 patients had complete and 1 patient had a partial response. No acute toxicity due to FSRT was observed in any cases.Conclusion: Stereotactic radiosurgery /radiotherapy provides acceptable toxicity and excellent local control results in patients with spinal cord tumors. However, well-designed studies with longer follow-up and a large number of patients are warranted.
Keywords: Cyberknife®; fractionated stereotactic radiotherapy; local control; spinal cord tumors; toxicity